Growth, Properties and Applications of Bi(0.5)Na(0.5)TiO(3) Ferroelectric Nanomaterials - Liu, Yuan (Nanomaterials (Basel), 2021)
The emerging demands for miniaturization of electronics has driven the research into various nanomaterials. Lead-free Bi(0.5)Na(0.5)TiO(3) (BNT) ferroelectric nanomaterials have drawn great interest owing to their superiorities of large remanent polarization, high pyroelectric and piezoelectric coefficients, unique photovoltaic performance and excellent dielectric properties. As attractive multifunctional ferroelectrics, BNT nanomaterials are widely utilized in various fields, such as energy harvest, energy storage, catalysis as well as sensing. The growing desire for precisely controlling the properties of BNT nanomaterials has led to significant advancements in material design and preparation approaches. BNT ferroelectric nanomaterials exhibit significant potential in fabrication of electronic devices and degradation of waste water, which pushes forward the advancement of the Internet of things and sustainable human development. This article presents an overview of research progresses of BNT ferroelectric nanomaterials, including growth, properties and applications. In addition, future prospects are discussed.